EFFECTIVENESS OF THE USE OF EDUCATIONAL INNOVATIONS IN TEACHING THE TOPIC OF POLYATOMIC ALCOHOLS - Nazarova Yulduz Atamuratovna; Professor Allaniyazova M. K.; Alauatdinov S. I. (Galaxy International Interdisciplinary Research Journal, 2024)
This article provides information on the use of new pedagogical technologies based on creativity in teaching the topic of alcohols in chemistry classes.